Combining user needs, lexicographic data and digital writing environments. (25th January 2020) - Frankenberg-Garcia, Ana
Abstract : The past decades have seen dramatic improvements to dictionary content and format. Yet dictionaries – both paper-based and digital – remain disappointingly underused. As a result, it is widely acknowledged that more needs to be done to train people in dictionary-consultation skills. Another solution would be to build lexicographic resources that require little or no instruction. In this paper, I present the ColloCaid project, whose aim is to develop a lexicographic tool that combines user needs, lexicographic data and digital writing environments to bring dictionaries to writers instead of waiting for them to get the information they need from dictionaries. Our focus is on helping writers produce more idiomatic texts by integrating lexicographic data on collocations into text editors in a way that does not distract them from their writing. A distinguishing characteristic of ColloCaid is that it is not limited to providing feedback on miscollocations. It also aims to 'feed forward', raising awareness of collocations writers may not remember or know how to look up. While our initial prototype is being developed specifically for academic English, the implications of our research can be broadened to other languages and usages beyond academic.